Chronic care handoffs in otolaryngology: Pediatric to Adult Care Providers. (July 2022) - Shearer, Jennifer; Cabrera, Claudia I.; Otteson, Todd; Howard, Nelson Scott
Abstract: Objective: The transfer of care from pediatric to adult otolaryngology remains unexplored. Our study investigated practice patterns among pediatric otolaryngologists. Methods: Twenty-question survey administered to otolaryngologists at the Society for Ear Nose and Throat Advancement in Children (SENTAC) and American Society of Pediatric Otolaryngology (ASPO) in December 2020 and July 2021 respectively. Data analyzed in RedCap including demographics, frequencies, means, and standard deviations. Results: The survey was completed by 48 participants. The majority of respondents practiced for at least 16 years (n = 28) at a University-based practices (n = 38), serving an entirely pediatric population (n = 44). Providers' expertise included chronic ear disease, voice disorders, and laryngeal stenosis. Few respondents (n = 12) had a transfer of care policy formalized at their practice. However, 38.8% of respondents were interested in developing one. Respondents rarely discussed topics such as drugs, tobacco, or alcohol use (mean 30.1%, SD 30.18%) with patients; and only 55.5% (SD 32.98) of providers asked patients 14 years and older to describe their condition, medications, or treatment plans. None of the providers were familiar with standardized transition of care tools. The majority of providers transferred patients between 18 and 25 years old to adult care. Conclusion: There is significant variation between otolaryngology providers' awareness and clinical practice patterns surrounding pediatric to adult transfer of care. Further studies are needed to evaluate the implications of these biases for patient outcomes and the opportunities for a standardized approach.